206k views
18 votes
Explain how you solved this problem.

Explain how you solved this problem.-example-1
User Njsf
by
5.2k points

2 Answers

3 votes
Start with PEMDAS.
Do (4+-2) (4+-2) (4+-2)
Then multiply your answer by 2, so you’ll have -2(8), which gives you -16,
Lastly you would have -4-16
And then your final answer would be -20
User Kevin Bayes
by
4.5k points
9 votes

Answer:

(-20)

Explanation:

-4 - 2(4 + (-2) )³ = -4 - 2(4 - 2)³

= -4 - 2*(2)³

= -4 - 2* 8

= -4 - 16

= -20

User Mpilquist
by
4.6k points